2012
DOI: 10.1096/fj.11-198515
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐31 targets FIH‐1 to positively regulate corneal epithelial glycogen metabolism

Abstract: Corneal epithelium relies on abundant glycogen stores as its primary energy source. MicroRNA-31 (miR-31), a corneal epithelial-preferred miRNA, negatively regulates factor inhibiting hypoxia-inducible factor-1 (FIH-1). Since HIF-1α is involved in anaerobic energy production, we investigated the role that miR-31 and FIH-1 play in regulating corneal epithelial glycogen. We used antagomirs (antago) to reduce the level of miR-31 in primary human corneal epithelial keratinocytes (HCEKs), and a miR-31-resistant FIH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 40 publications
3
49
0
Order By: Relevance
“…Interestingly, expression profiling indicated that with respect to the ocular anterior segmental epithelium, miR-31 is a corneal epithelial-preferred miRNA (32). As described previously, FIH-1 protein is abundantly detected in human limbal epithelium but not in human corneal epithelium (12). We propose that low levels of miR-31 and correspondingly high levels of FIH-1, which attenuates Notch signaling, may be one mechanism that maintains the relatively undifferentiated phenotype characteristic of limbal epithelial basal cells (20).…”
Section: Mir-31/fih-1 Nexus Contributes To Corneal Epithelial Morphogsupporting
confidence: 56%
See 3 more Smart Citations
“…Interestingly, expression profiling indicated that with respect to the ocular anterior segmental epithelium, miR-31 is a corneal epithelial-preferred miRNA (32). As described previously, FIH-1 protein is abundantly detected in human limbal epithelium but not in human corneal epithelium (12). We propose that low levels of miR-31 and correspondingly high levels of FIH-1, which attenuates Notch signaling, may be one mechanism that maintains the relatively undifferentiated phenotype characteristic of limbal epithelial basal cells (20).…”
Section: Mir-31/fih-1 Nexus Contributes To Corneal Epithelial Morphogsupporting
confidence: 56%
“…The limbal epithelium, which is the preferential site of the corneal epithelial stem cells (20,28), interestingly has high levels of FIH-1 expression compared with the corneal epithelium (12). In concert with a lack of FIH-1 staining in the limbal epithelium (Fig.…”
Section: Fih-1 Expression Is Elevated In Conditions Of Abnormal Epithmentioning
confidence: 93%
See 2 more Smart Citations
“…microRNAs (miRNAs) are small, noncoding RNA molecules found in multicellular eukaryotes and play essential regulatory roles in translational repression (15). Several wound healing-related miRNAs, such as miR-146a, were identified in the corneas of people with diabetes (14,16,17). Abnormal miR-146a upregulation may be an important mechanism of delayed wound healing in the diabetic cornea (17,18).…”
mentioning
confidence: 99%